Microscopic and endoscopic “chopstick” technique removal of choroid plexus papilloma in the third ventricle of an infant: a case report with systematic review of literature - Li, Weiwei; Li, Zongping; Wei, Chengyan; Yang, Xiaoyong; Ji, Yuzhu; Liu, Hongyuan (Frontiers in Oncology, 2023)
Choroid plexus papilloma (CPP) is rare and even rarer in infants and young children, and it usually occurs in the ventricles. Due to the physical peculiarities of infants, tumor removal by microscopic or endoscopic surgery alone is difficult. CASE PRESENTATION: A 3-month-old patient was found to have an abnormally enlarged head circumference for 7 days. Cranial magnetic resonance imaging (MRI) examination revealed a lesion in the third ventricle. The patient underwent combined microscopic and endoscopic "chopstick" technique to remove the tumor. He recovered well after the surgery. Postoperative pathological examination revealed CPP. Postoperative MRI suggested total resection of the tumor. Follow-up for 1 month showed no recurrence or distant metastasis.CONCLUSIONS: Combined microscopic and endoscopic "chopstick" technique may be a suitable approach to remove tumors in infant ventricles.